2022
DOI: 10.1002/admi.202201320
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam as Straightener to De‐Wrinkle Large 2D Black Phosphorus Flake: An In Situ TEM Monitoring

Abstract: originating from the nonuniform interlayer spacing of a wrinkled 2D structure leads to alteration in band structure and eventually restricts from attaining ideal experimental conditions. [15][16][17] Due to the atomically thin dimension, it is practically impossible to polish out the irregularities by physical or chemical means, as standardized in conventional silicon process flow. Quite a few efforts were made to develop post-synthesis process for minimizing surface corrugations on 2D crystal, however, most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Kaur et al demonstrated a straightening method to smoothen and de-wrinkle of 2D BP flakes via electron beam irradiation to improve crystallinity and remove line defects from the lattice. [143] The ironing of BP using electron beam irradiation enabled to control the stress in lattice and the buckling structure of the flake, which can be an important moving forward for controlling 2D atomic nanostructure. Another novel way to enhance optoelectronic properties for PD applications is using hybrid heterostructures.…”
Section: Bpmentioning
confidence: 99%
“…Kaur et al demonstrated a straightening method to smoothen and de-wrinkle of 2D BP flakes via electron beam irradiation to improve crystallinity and remove line defects from the lattice. [143] The ironing of BP using electron beam irradiation enabled to control the stress in lattice and the buckling structure of the flake, which can be an important moving forward for controlling 2D atomic nanostructure. Another novel way to enhance optoelectronic properties for PD applications is using hybrid heterostructures.…”
Section: Bpmentioning
confidence: 99%